The impact of a pandemic on entrepreneurial behaviour: A qualitative study of wedding vendors - D.A.J. Bornman; L. Steenkamp (Cogent Business & Management, 2023)
The aim of this study is to determine what changes wedding vendors had to make to survive the global COVID-19 pandemic. Specific focus was placed on how wedding vendor entrepreneurs use creativity, innovation, networking and advertising as a competitive advantage. Qualitative research was conducted which reflects individuals' perspectives, beliefs, attitudes and experiences. Semi-structured interviews took place electronically through online voice calling due to the global pandemic. The individual participants, each representing their own business, were interviewed to gain a better understanding of entrepreneurship in the wedding industry. It is evident that all the vendors adapted during the global COVID-19 pandemic, and that dealing with future opportunities by linking these to loyalty and creativity are essential aspects of entrepreneurship in the wedding industry. The global pandemic proved the importance of how the wedding industry is dynamic where individuals are required to wear different hats and be flexible, as businesses were forced to adapt and reposition themselves during and after COVID-19 as a method of survival. It is recommended that vendors ensure the utilisation of existing resources and branch off into new avenues-not necessarily entering into new markets or new industries, but rather focusing on complementary products or services.
Keywords: 650; Covid-19; creativity; Entrepreneurship; innovation; qualitative research; wedding industry; wedding vendors